Reputation and trust management in heterogeneous peer-to-peer networks - Chu, Xiaowen; Chen, Xiaowei; Zhao, Kaiyong; Liu, Jiangchuan (Telecommunication systems, 2010)
In a heterogeneous ubiquitous peer-to-peer network, different peers may provide different qualities of service, and hence it is very important and helpful to identify those peers that can provide better services than others. In this paper, we use a reputation value to represent the quality of service offered by a peer. We design a novel reputation model which enables any peer to calculate the reputation value of any other peer, so as to differentiate peers that provide good quality of service from peers that provide poor or even faulty service. In order to speed up the convergence of reputation calculation, a peer collects recommendations from its neighbor peers. On the other hand, in order to overcome the problem of malicious recommendations, we propose an auxiliary trust mechanism which calculates a trust value for each peer. Our experimental results show that the reputation model achieves a fast convergence speed, and it is robust against a large portion of malicious peers that provide fraud recommendations.